Metodologia para desenvolvimento de projeto de forno de carbonização transportável - Biscaia, Ricardo Vinicius Bubna (2021)
The transport of wood from the forest to the carbonization areas impacts the operational cost for the production of charcoal, in addition to limiting viable economic radius for the wood acquisition. The sale value of charcoal, used as a reducer by the steel industry is directly associated with changes in the price of pig iron (commodity), as it is the highest cost input for its production. Therefore, it is considered necessary to improve charcoal production processes, through the development of kiln alternatives that meet the specific needs of producers. In the initial stages of new product development, many criteria that are relevant to customers, however, which depend on the product's performance to be measured, are disregarded. Therefore, the objective of this work was to create a methodology for the development of a transportable kiln project, in order to reduce costs with transporting wood to the carbonization squares, considering kiln performance estimates to select the most adequate conceptual project to the needs of decision makers. The methodology for the development of the kiln conceptual design comprised: i) characterization of commercially available, patented charcoal kilns; ii) definition of relevant criteria for selecting transportable kiln design variables; iii) development of transportable kiln alternatives; iv) application of a Trapezoidal Bipolar Fuzzy TOPSIS decisionmaking method associated with the Bestworst method for weighting. The decision method was evaluated by a univariate sensitivity analysis, in order to identify the behavior of the applied method responses, as a function of the criteria weights variation and a design FMEA was developed to reduce identified risks in the design. Six alternatives for transportable kiln projects were developed with different constructive structures and applied materials. The decision method ranked the alternatives according to the interests of three decision makers. The results allowed to order the alternatives of conceptual projects through a selection adjusted to the interests of decision makers. The sensitivity analysis showed that the method indicates that changing the priorities of decision makers in relation to the criteria can form another ranking to adjust to the new interests of these decision makers. A conceptual design of a transportable kiln was developed with a methodology that contributes to cost reduction during the initial stages of product development, as it directs towards the design alternative that is most likely to meet the expectations of the consulted customers/decision makers.